Zeitliche Entwicklung der Wassermassen-Eigenschaften im subpolaren Nordatlantik aus Argo Analysefeldern - Doejen, Thomas (2012)
This work focusses on water mass changes in the subpolar North Atlantic (SPNA) for the period 2004 to 2011. Water masses and processes which are part of these region play an important role in the global climate system. Diversity and long term oscillation of water mass properties will occur to changes in climate, which to predict are of big interest. The aim of this work is to study modification of the upper 2000 m hydrographic characteristics and forces which influence these modification. Therefore temperature and salinity differences are calculated in different pressure levels to supply an overview to changes in the whole area. To identify temporal development of different regions in the SPNA the heat content anomaly was computed. Also the sections AR7W and AR7E which are known from the World Ocean Circulations Experiment (WOCE) were constructed to show water mass differences in time. The result from calculation shows light warming and an increase in salinity in deeper parts and cooling and a decrease in salinity at sea surface. The warming seems to spread easterly with an increase in depth. Between the pressure level of 1000-1500 dbar a bisection can be found where the western part attend to warming and an increase of salinity, while the eastern part is cooled and less saline. Nearly the entire SPNA shows warming and an increase of salinity at 1500-1975 dbar. The North Atlantic Oscillation (NAO) plays an important role in ocean atmospheric interaction for the SPN A, so the NAO index demonstrates close relationship to changes in water mass properties. Deep water convection which regulates cold freshwater injection in the Labrador Sea seems to be linked to the NAO index. Missing of deep water convection > 1000 m in past years can be seen as a reason for warming in intermediate water masses at the Labrador Sea. These water masses are slowly spreading eastwards. This work is based on an existing global gridded Argo data set. This data set was composed with Argo floats and reach down to a pressure level of 1975 ...